Major viruses affecting food legumes in Morocco - Bencheqroun, Sanae Krimi; Kumari, Safaa; Moukahel, Abdulrahman; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Food legumes play an important role in Morocco's agricultural landscape. They cover approximately 270,000 hectares, representing 4% of the total agricultural area. The productivity of food legumes has persistently remained low and variable, primarily attributed to the susceptibility of the crop to environmental stresses, diseases, insect pests, and parasitic weeds. To set priorities for the development of new varieties and disease management, status and identification of viruses affecting legume crops is essential in the different production areas. Accordingly, surveys of food legume viruses were conducted during February and March 2023 in regions of Doukkala and Chaouia, Morocco. A total of 288 plants from 39 fields were collected and tested by TBIA using 7 specific antibodies. Results showed that BLRV and BYMV were the most common viruses affecting lentil, faba bean and chickpea in the two surveyed provinces. CpCSV, BWYV and FBNYV were detected also but in low incidence.